(untitled) (Research, Society and Development, 2020)
The aim of this study was to verify through personal and environmental factors which are the predictors of recent stress in nursing students. This is a cross-sectional study with a quantitative approach. For data collection, we used Sociodemographic Questionnaire, Stress Symptom Inventory (ISSL) for recent stress, Childhood Trauma Questionnaire (CTQ), Perceived Stress Scale (PSS-14) and Rosenberg Self-Esteem Scale. To verify the predictor variables of recent stress, the statistical analysis used binary logistic regression. The study was attended by 209 college students. Physical activity, smoking, high self-esteem, early stress and religion were pointed as predictors of recent stress. Average and high perception of stress, being married, working, working in health care, weekly leisure activities represented lower chances for stress. The identification of stress predictor variables helps in the elaboration of the profile of college students most vulnerable to stress.